1998
DOI: 10.1590/s0074-02761998000700016
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic features associated with susceptibility and resistance of biomphalaria snails to infection with Schistosoma mansoni

Abstract: Resistance and susceptibility of Biomphalaria snails to Schistosoma mansoni sporocysts occur in different degrees. Histopathology reflects these diferences. In a state of tolerance numerous sporocysts in different stages of differentiation are seen in the absence of host tissue reaction. However extensive diffuse and focal proliferation of amebocytes with sequestration and destruction of many parasitic structures appear in resistant snails. Some snails are totally resistant and when exposed to infecting miraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…4. Studies using different populations/strains of Biomphalaria and Schistosoma mansoni reported the variability in host responses, according to their geographical origin and species (Newton 1952;Guaraldo et al 1981;Godoy et al 1997;Borges et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…4. Studies using different populations/strains of Biomphalaria and Schistosoma mansoni reported the variability in host responses, according to their geographical origin and species (Newton 1952;Guaraldo et al 1981;Godoy et al 1997;Borges et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…When the hemocytes concentrate around the larvae they form granuloma type structures (Borges et al 1998). The hemocytes are small phagocytic cells with basophil cytoplasm and varied forms, due to pseudopodia emission.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin-eosin-stained 5-µM sections were examined microscopically for the histological condition of larval trematodes, as categorized by Borges et al (1998). Histological analysis was performed on about 38 and 45 susceptible and resistant snails, respectively.…”
Section: Light Microscopymentioning
confidence: 99%